2017
DOI: 10.2147/ijn.s114885
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine induction of sol&ndash;gel-derived TiO<sub>2</sub> and SiO<sub>2</sub> coatings on metallic substrates after implantation to rat femur

Abstract: Material surface is a key determinant of host response on implanted biomaterial. Therefore, modification of the implant surface may optimize implant–tissue reactions. Inflammatory reaction is inevitable after biomaterial implantation, but prolonged inflammation may lead to adverse reactions and subsequent implant failure. Proinflammatory activities of cytokines like interleukin (IL)-1, IL-6, and tumor necrosis factor-alpha (TNF-α) are attractive indicators of these processes and ultimately characterize biocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…30,31 Non-toxic effect of silica and zirconia layers was established using both in vitro and in vivo models. [32][33][34] Moreover, silica and zirconia sol-gel coatings were also recognized as biocompatible with osteoinductive potential. 34,35 In addition, we previously showed that hybrid sol-gel coating SiO 2 /ZrO 2 ameliorates the osteogenic differentiation of multipotent mesenchymal cells (MSCs) of both bone marrow and adipose tissue origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Non-toxic effect of silica and zirconia layers was established using both in vitro and in vivo models. [32][33][34] Moreover, silica and zirconia sol-gel coatings were also recognized as biocompatible with osteoinductive potential. 34,35 In addition, we previously showed that hybrid sol-gel coating SiO 2 /ZrO 2 ameliorates the osteogenic differentiation of multipotent mesenchymal cells (MSCs) of both bone marrow and adipose tissue origin.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Moreover, silica and zirconia sol-gel coatings were also recognized as biocompatible with osteoinductive potential. 34,35 In addition, we previously showed that hybrid sol-gel coating SiO 2 /ZrO 2 ameliorates the osteogenic differentiation of multipotent mesenchymal cells (MSCs) of both bone marrow and adipose tissue origin. 11 Combination of progenitor cells, capable of functional differentiation toward bone forming cells with osteoinductive SS316L matrices provides a promising strategy for bone tissue engineering and cellular delivery, thus opens range of new perspective of clinical applications in bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of cytokines not only reflects the presence and intensity of the inflammation reaction, but also plays an important role in tissue damage and chronic pain. Therefore, these cytokines are attractive markers to estimate the tissue responses to the sustained release formulations 64 .…”
Section: Resultsmentioning
confidence: 99%
“…[53] Recently, Sr, Cu, and Si also have been incorporated on the Ti implants in the form of 3D or mesoporous structures using sol-gel route. [55][56][57][58][59]…”
Section: Compositing With Polymersmentioning
confidence: 99%
“…[24,157] Moreover, the inflammatory response is demonstrated to reduce on the SiO 2 coatings. [57] Wang et al have reported that Si-incorporated NTs coating prepared by anodization and EBE methods improve spreading, osteogenesis, and differentiation of MC3T3-E1 cells. In particular, the sample with the largest amount of Si (5.93% Si) shows the best ALP activity, osteogenesis-related gene expression, and mineralization (Figure 11).…”
Section: Si-incorporated Coatingmentioning
confidence: 99%